Do family physicians with focused practice or Care of the Elderly training practice differently than others? A population-based, propensity score-matched cohort study - Rebecca H. Correia; David Kirkwood; Aaron Jones; Henry Yu-Hin Siu; Meredith Vanstone; Steve Slade; Andrew P. Costa (PLoS ONE, 2026)
Background Family physicians play a key role in the care of older adults, yet the impact of additional geriatric training or focused practice remains unclear. Objective We compared performance on established clinical practice measures among family physicians with/without evidence of elderly-focused practice or training. Methods We used linked administrative data to conduct a population-based, propensity score-matched cohort study. Participants included family physicians in Ontario, Canada with rostered patients in 2019. Using logistic regression, we established propensity scores to match physicians with a focused alternative funding plan and/or a Certificate of Added Competence in ‘Care of the Elderly’ at a 1:4 ratio to a control group without focused practices or added competence certificates. We compared 11 practice-based measures endorsed by Canadian clinicians and researchers, adjusting for physician factors, medical practice characteristics, and primary care activities. Results We identified 232 family physicians with elderly-focused practices or training and 928 comparable controls. While differences in study group clinical practices were not statistically significant for most processes, they were in three areas. More physicians with elderly-focused practice or training conducted testing aligned with the most recent Canadian Consensus on Dementia and were more likely to prescribe potentially inappropriate medications and antipsychotics to older attached patients. Conclusions We observed limited to no differences in clinical practice measures between family physicians with ‘Care of the Elderly’ focused practice or certification to those without. The lack of differences may reflect true performance, the effect of uniform constraints of primary care practice, or inherent limitations of objective performance measurement.